Caracterização da transmissão dopaminérgica na linhagem SHR – um novo modelo para o estudo da esquizofrenia - Santos, Camila Mauricio [UNIFESP] (2011)
Schizophrenia is the most serious mental illness, ranked as the fourth worldwide cause of disability according to World Health Organization. Although the pathophysiology of schizophrenia is not completely elucidated it is well- established that dysfunctions in the dopaminergic transmission are involved. Our group suggests the SHR strain as a model to study several aspects of schizophrenia, based on behavioral changes and pharmacological responses observed in previous studies. These behavioral changes are specifically reversed by antipsychotics and aggravated by proschizophrenia manipulations. The aim of this work was to characterize different parameters of dopaminergic transmission in the SHR strain in brain structures associated with schizophrenia. We used autoradiography and immunohistochemistry analyses to quantify respectively D1 receptors and enzymes related to the synthesis and degradation of dopamine. There was a decrease in the number of D1 receptors in the prefrontal cortex of SHR. With the immunohistochemical analysis we observed an increase in the amount of COMT enzyme in the core portion of the nucleus accumbens and a decrease in the stained area on the dorsal striatum in SHR. There was no difference between strains on the amount of MAO in the analyzed regions. In the context of the pathophysiology of schizophrenia, the decrease of D1 receptors in the prefrontal cortex is consistent with the proposed cortical dopaminergic hypofunction via D1 receptors. Furthermore, the decreased stained area in the dorsal striatum in SHR may be the result of a structural change in the cortico-striatal dopaminergic pathway. These results present further evidence strengthening the SHR strain as an animal model for the study of schizophrenia.